Effect of Cnidoscolus Aconitifolius leaf extract on the blood glucose and insulin levels of inbred type 2 diabetic mice - Oladeinde, F.O.; Kinyua, A.M.; Laditan, A.A.; Michelin, R.; Bryant, J.L.; Denaro, F.J.; Makinde, J.M.; Williams, A.L.; Kennedy, A.P.; Bronner, Y. (Cellular and Molecular Biology, 2007)
The effects of Cnidoscolus aconitifolius (CA) leaf extract and chlorpropamide on blood glucose and insulin levels in the inbred type 2 diabetic mice are reported. After treatment with CA, the glucose levels were measured at 0 and 2-hour intervals in experimental groups and controls. Group I received no treatment and served as control; Group II was the reference and it received chlorpropamide; Groups I-III were moderately diabetic, 100-300 mg/dL blood glucose levels while Group IV were severely diabetic (> 300 mg/dL). Groups III and IV received CA and served as test groups. There was no significant difference between the blood glucose levels at 0 and 2 hours for the control group, (P>0.23) but there were statistically significant differences for Group II (P<0.0002); Group III (P<0.002) and Group IV (P<0.0001). For moderately diabetic mice, CA and chlorpropamide decreased the glucose levels by 25.6% and 16.3% respectively while for the severely diabetic mice CA decreased the blood glucose by 43.7%. It is proposed that CA has an insulinogenic property that possibly stimulated dormant Î²-cells to secrete insulin. The histopathology of several organs in the treated animals was found to differ from the expected. The islets of Langerhans for example were found to be preserved in the time frame examined. Also the liver and kidney were found to display milder pathology in the treated groups.